Biofortified Mustard, Socio-Technical Innovation Bundling Approach: Empowering Women and Nurturing Resilience - Jain, Anusha; Joshi, Garima; Chadha, Deepali; Mukhopadhyay, Prama; Gartaula, Hom N.; Puskur, Ranjitha (CGIAR Initiative on Gender Equality, 2024)
Promising innovations often face challenges due to the absence of a conducive environment for development and widespread adoption. It is crucial to identify socio-technical bundles of innovations to unlock the transformative capabilities of emerging technologies. Within the realm of technical innovations in agriculture, with a particular focus on their appropriateness for women farmers, this case study explores the socio-technical dimensions of the adoption of biofortified mustard (BFM) among women farmers in Uttar Pradesh, India. The initiative is part of a broader strategy that aims to promote nutrition-focused and gender-responsive agricultural practices. The study analyzes the factors that led to the advancement of a biofortified mustard (BFM) variety from lab to land and the role different ecosystem actors played to that enable farmers to realize its benefits and adopt the innovation. The outcomes observed in the intervention group underscore the adaptability and resilience of BFM, challenging established norms in traditional cultivation practices such as limited crop diversity, susceptibility to climate change, and resource-intensive methods. Despite initial skepticism among the farmers, positive outcomes sparked broader interest, emphasizing the role of information dissemination. Self-Help Groups (SHGs) and Farmer Producer Organizations (FPOs) emerged as pivotal in empowering women and fostering community engagement as did research institutions that worked towards agricultural innovation and the advocacy of best practices. The intervention led to collaborative efforts involving SHGs, FPOs, government agencies, extension agents, and research institutes. In contrast, the non-intervention group faced barriers, highlighting the need for targeted interventions and support mechanisms. The findings suggest that the effective scaling of technological innovations, like BFM, is more likely when combined with social interventions and an enabling ecosystem driven by policy. In the current intervention, leveraging group membership, actively engaging community mobilizers, and ensuring thorough gender sensitization of all stakeholders are key strategies to promote gender inclusivity in transforming agricultural systems. However, the lack of a comprehensive ecosystem, particularly in creating market demand and facilitating necessary infrastructure, remains a barrier to the intervention's successful adoption and scaling.